BIOLOGICAL STUDIES OF 4-AMINO BENZAMIDE DERIVED 1,2,3-TRIAZOLE LINKED CHALCONE AND ITS PYRAZOLINE DERIVATIVES - S, SATHIYA; BS, KRISHNAMOORTHY; S, MEENACHI; R, RAVIKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The present work planned to investigate the anti-bacterial, anti-fungal, and anti-oxidant activity against 4-amino benzamide derived 1,2,3-triazole linked chalcone and pyrazoline derivatives. Methods: Anti-microbial activity for pyrazoline derivatives was accomplished by serial dilution method. The test organisms of bacterial strains were (Enterococcus faecalis, Staphylococcus aureus, Klebsiella pneumoniae, and Pseudomonas fluorescence) and the fungal cultures (Aspergillus niger, Aspergillus terreus, and Trichoderma harzanium). The method used in the anti-oxidant activity is 2,2-diphenyl-1-picrylhydrazyl (DPPH) and nitric oxide scavenging method. Results: All the compounds showed good to moderate anti-bacterial and anti-fungal activities. The results of IC50 values showed lower potent inhibition activity with DPPH and higher potent inhibition activity in nitric oxide scavenging method. Conclusion: All the compounds had exhibited capricious growth inhibitory effect on anti-bacterial, anti-fungal, and anti-oxidant activities.